Transdentinal cytotoxicity of glutaraldehyde on odontoblast-like cells. Issue 8 (August 2015) - Scheffel, Débora Lopes Salles; Soares, Diana Gabriela; Basso, Fernanda Gonçalves; de Souza Costa, Carlos Alberto; Pashley, David; Hebling, Josimeri
Abstract Objectives This study investigated the transdentinal cytotoxicity of glutahaldehyde-containing solutions/materials on odontoblast-like cells. Methods Dentin discs were adapted to artificial pulp chambers. MDPC-23 cells were seeded on the pulpal side of the discs and the occlusal surface was treated with the following solutions: water, 2% glutaraldehyde (GA), 5% GA, 10% GA, Gluma Comfort Bond + Desensitizer (GCB + De) or Gluma Desensitizer (GDe). Cell viability and morphology were assessed by the Alamar Blue assay and SEM. The eluates were collected and applied on cells seeded in 24-well plates. After 7 or 14 days the total protein (TP) production, alkaline phosphatase activity (ALP) and deposition of mineralized nodules (MN) were evaluated. Results Data were analyzed by Kruskal-Wallis and Mann-Whitney tests (p < 0.05). GA solutions were not cytotoxic against MDPC-23. GCB + De (85.1%) and GDe (77.2%) reduced cell viability as well as TP production and ALP activity at both periods. After 14 days, GCB + De and GDe groups produced less MN. Affected MDPC-23 presented deformation of the cytoskeleton and reduction of cellular projections. Conclusions The treatment with 2.5%, 5% and 10% GA was not harmful to odontoblast-like cells. Conversely, when GA was combined with other components like HEMA, the final material became cytotoxic. Clinical significance Glutaraldehyde has been used to decrease dentin hypersensitivity. This substance is also capable of preventing resin-dentin bond degradation by cross-linking collagen and MMPs. This study showed that GA might be safe when applied on acid etched dentin. However, when combined with HEMA the product becomes cytotoxic.